Increasing Heart Dose Reduces Overall Survival in Patients Undergoing Postoperative Radiation Therapy for NSCLC - Annemarie F. Shepherd, MD; Anthony F. Yu, MD; Michelle Iocolano, MD; Jonathan E. Leeman, MD; Aaron T. Wild, MD; Brandon S. Imber, MD, MA; Jamie E. Chaft, MD; Michael Offin, MD; James Huang, MD; James M. Isbell, MD, MSCI; Abraham J. Wu, MD; Daphna Y. Gelblum, MD; et al. (JTO Clinical and Research Reports, 2021)
Introduction: Given the concern for cardiopulmonary toxicity in patients with NSCLC undergoing postoperative radiation therapy (PORT), the purpose of this study was to evaluate the association between heart dose and overall survival (OS) in patients undergoing PORT with modern techniques. Methods: This is a retrospective study of consecutive patients with NSCLC treated with PORT between May 2004 and January 2017. Clinical records were reviewed and radiation dose distributions were analyzed for association with OS. Results: A total of 284 patients were analyzed. At the time of surgery, most patients had pathologic American Joint Committee on Cancer seventh edition stage III disease (91.2 %) and received either preoperative or adjuvant chemotherapy (92.3 %). Most patients underwent a lobectomy (81.3 %) and had R0 (80.6 %) or R1 (19.4 %) resection. PORT was delivered with a median radiation dose of 54 Gy, and 70.4 % of patients were treated with intensity-modulated radiation therapy. Dosimetric variables across a large range of doses to the heart were highly significant (p < 0.05) for OS. The volume of the heart receiving 8 Gy (HV8) was the most significant dosimetric variable (p < 0.001), and the median HV8 was 35.5 %. The median OS was 33.2 versus 53.6 months (p < 0.005) for patients with HV8 above or below 35.5 %, respectively. On multivariable analysis accounting for other potential prognostic confounders, HV8 remained highly significant (p < 0.001). Conclusions: The data reveal a strong correlation between increasing heart dose and OS in patients with NSCLC undergoing PORT. Taken together with the recently presented LungART trial, lowering heart dose in PORT patients may help to decrease the risk of morbidity and mortality and improve the therapeutic ratio of PORT.